Pengembangan modul ajar Pancasila berbasis kurikulum merdeka fase A di SD Laboratorium UM - Munawwaroh, Isti (Maliki Interdisciplinary Journal, 2024)
Teaching modules are teaching modules which are part pf the teaching materials. These curriculum-based teaching modules can be interpreted as implementing learning outcomes or learning outcomes (CP), then depelop into learning objectives (ATP) in the pancasila profile. Based on the result of interviews with UM Laboratory Elementary School class teachers, problems were found in the form of difficulties in developing PPKN teaching materials and students were also having problems implementing pancasila material in PPKN learning. Based on these problems, researchers develop a pancasila and citizenship teaching module at stage A. The research method used was research and Development (R&D) which was limited to testing product validity. The result of this research were the development of the pancasila and citizenship teaching module (PPKN) phase A. The research subject were firts grade teachers and several first grade students. The percentage of velidation results from material/ content experts was 84% valid and design experts were 88.8% valid.